2006
DOI: 10.1007/s00204-006-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cypermethrin and methyl parathion mixtures on hormone levels and immune functions in Wistar rats

Abstract: To study interaction and dose-related effects of mixed cypermethrin and methyl parathion on endocrine and immune functions, 120 Wistar rats were divided randomly into six groups of ten male and ten female rats, respectively, at the age of 2 months. All groups were force-fed every 2 days for 30 days with cypermethrin 0.0, 8.0, 0.0, 8.0, 1.8, 0.4 mg/kg bw and methyl parathion 0.0, 0.0, 0.23, 0.23, 0.0518, 0.0115 mg/kg bw. Controls received vehicle solvent only. Body weight gain and organ weights were measured. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Wang et al [43] observed a dose-dependent decrease in T 4 and T 3 and elevation in TSH in permethrin-treated rats; however, with deltamethrin, the only alteration was the decrease of T 4 levels. Similar results were observed with bifenthrin and Lambda-cyhalothrin [44], and recently, Liu et al [45] observed the same trend in Wistar rats treated with cypermethrin plus methyl parathion. These diverse results might be stemmed from the different study designs with respect to the dose, route, and length of insecticide treatment, as well as the sex, species, and strain differences of used animals.…”
Section: Discussionsupporting
confidence: 82%
“…Wang et al [43] observed a dose-dependent decrease in T 4 and T 3 and elevation in TSH in permethrin-treated rats; however, with deltamethrin, the only alteration was the decrease of T 4 levels. Similar results were observed with bifenthrin and Lambda-cyhalothrin [44], and recently, Liu et al [45] observed the same trend in Wistar rats treated with cypermethrin plus methyl parathion. These diverse results might be stemmed from the different study designs with respect to the dose, route, and length of insecticide treatment, as well as the sex, species, and strain differences of used animals.…”
Section: Discussionsupporting
confidence: 82%
“…Cypermethrin and mancozeb are the two widely used pesticides worldwide in agriculture, households, and industries due to their low mammalian toxicity and short environmental persistence (Hasan, 2010;Hayes & Laws, 1990;Lorgue & Lechenet, 1996). Cypermethrin is a synthetic pyrethroid insecticide which showed significant effects on hematological (Kamal et al, 2007;Nair et al, 2010;Sayim et al, 2005;Yousef et al, 2003) and immunological parameters (Desi et al, 1986;Liu et al, 2006;WHO, 1989) in sub-chronic repeated dose studies in animals. Mancozeb, ethylenebisdithio carbamate, is another pesticide used extensively and reported to have adverse effects on various hematologic (Myoung-yun & Cheong, 2004;Wael, 2012) and immunologic parameters (Corsini et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Its low sensitivity in mammals ensures low acute toxicity. Recently, animal and in vitro studies suggest that some PYRs may disrupt the immune function, 50,51) produce oxidative stress, [52][53][54][55] and possess male reproductive toxicity by disrupting testosterone biosynthesis due to diminishing the delivery of cholesterol into the mitochondria and the conversion of cholesterol to pregnenolone in Leydig cells. 56) Moreover, it has been reported that the PYR metabolites, 3-PBAlc and 3-PBAld, possess estrogenic activity of approximately 10 5 less than that of 17b -estradiol.…”
Section: Results Unitsmentioning
confidence: 99%